Effect of alemtuzumab over sNfL and sGFAP levels in multiple sclerosis - Sainz-Amo, Raquel; Rodero Romero, Alexander; Monreal, Enric; Chico García, Juan Luis; Fernández Velasco, José Ignacio; Villarrubia, Noelia; Veiga González, Jose Luis; Sainz de la Maza, Susana; Rodríguez Jorge, Fernando; Masjuan, Jaime; Costa-Frossard, Lucienne; Villar, Luisa María (Frontiers in Immunology, 2024)
Introduction Alemtuzumab is a highly effective pulsed immune reconstitution therapy for multiple sclerosis (MS). Aim To evaluate serum neurofilament light chain (sNfL) and serum glial fibrillary acidic protein (sGFAP) in patients with relapsing-remitting MS who have been treated with Alemtuzumab over the course of 2 years. Methods This prospective study involved MS patients treated with Alemtuzumab at a referral MS center. Both sNfL and sGFAP were analyzed at baseline and then again at 6, 12, and 24 months post-treatment using the single molecule array (SiMoA) technique. We also recruited matched healthy controls (HCs) for comparison. Results The study included 46 patients (with a median age of 34.2 [Interquartile range (IQR), 28.7–42.3] years, 27 of which were women [58%]) and 76 HCs. No differences in demographic characteristics were observed between patients and HC. The median disease duration was 6.22 (IQR, 1.56–10.13) years. The median annualized relapse rate before treatment was 2 (IQR, 1–3). At baseline, sNfL and sGFAP levels were higher in MS patients (median of 18.8 [IQR, 10.7–52.7] pg/ml and 158.9 [IQR, 126.9–255.5] pg/ml, respectively) when compared to HC (6.11 [IQR, 2.03–8.54] pg/ml and 91.0 [72.6–109] pg/ml, respectively) (p<0.001 for both comparisons). The data indicates that 80% of patients had high (≥10 pg/ml) sNfL values at baseline. We observed a significant decrease in sNfL levels at 6 (65%, p = 0.02), 12 (70.8%, p<0.001), and 24 (78.1%, p<0.001) months. sNfL reached similar levels to HC only after 24 months of Alemtuzumab treatment. During the follow-up period, no changes were identified in the sGFAP values. Conclusion Alemtuzumab leads to the normalization of sNfL values in MS patients after 2 years of treatment, with no apparent effect on sGFAP values.